In relation to the division of transporting work in the system public passenger transport - Доля, Костянтин Вікторович (Eastern-European Journal of Enterprise Technologies, 2011)
Distributing of transporting work is considered in the system of public passenger transport for existent directions of payment of travel. The structure of Organ of management by a transport is offered